Ku Anis Cake & Bakery / Nik Nurnina Anis Alya Nik Man - Nik Man, Nik Nurnina Anis Alya (2020)
The content in this case study is included about the entrepreneur and business profile. Then, in this case study, it is also include entrepreneurial characteristics. I also stated the pictures that associated with the bakery in the appendices section. Based on case study, I need to find a business that their sales not exceed RM250 000 in a year. So, I decided to choose one small bakery business that called Ku Anis Cake & Bakery for my case study. Ku Anis Cake & Bakery is a business that offering many various types of foods such as cakes, bread, cookies and so on that targeted for all people especially to the people who lived in Kota Bharu, Kelantan. As I know, the main product of this bakery is cakes. This bakery is a small to medium local bakery shop which is being operated by owner namely, Tengku Anis with 6 employees depending upon the season as well as the workload in the bakery. I believe that Ku Anis Cake & Bakery is one of the famous bakery in Kota Bharu because of the uniqueness of the cake that produced by the owner of the bakery herself.